The relationship between Brand Identity Planning model and Brand Equity model of local denim brands in Pakistan - Karim, Muhammad Ahsan (2011)
The following study is conducted to find the relationship between the Brand Equity and Brand Identity Planning model for the local denim brands of Pakistan. This research is done to help understand the importance of the two models in the field of branding and how these models could help the local denim brands of Pakistan grow for their future endeavors.Both the models discussed in this study are the work of the renowned branding guru Mr. David Aaker himself. The models could be used by the local denim brands to make them of international standards and improve their profitability.The models were discussed at length and then variables were analyzed and formed. A questionnaire was designed to collect the data which was coded using the SPSS software for results compilation. The findings suggest that there was a positive correlation between the models. The results were analyzed to help understand the importance of the two models for the local denim brands of Pakistan. There still is room for a lot of growth in the retailing sector of local denim brands and their profitability could be increased with the effective use of these models.